Manajemen Komunikasi Krisis Era Transparansi Radikal: Integrasi Data Visual Real-Time sebagai Instrumen Restorasi Reputasi dalam Industri AMDK - Brilian Prabasari; Sindy Dwi Kurnia; Marjam Desma Rahadhini (CV. Aksara Global Akademia, 2026)
The phenomenon of radical transparency in the Bottled Drinking Water (AMDK) industry in 2025 triggered a reputation crisis and a massive erosion of customer loyalty. This crisis began with negative sentiment on social media that led to surprise inspections by regulatory authorities of the industry leader's